2018
DOI: 10.1007/s40520-018-0905-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery—ERAS—principles, practice and feasibility in the elderly

Abstract: This is a short overview of the principles of a novel development in surgery called enhanced recovery after surgery (ERAS) programs. This is an evidence-based approach to perioperative care that has shown to reduce complications and recovery time by 30–50%. The main mechanism is reduction of the stress reactions to the operation. These principles have been shown to be particularly well suited for the compromised patient and hence very good for the elderly people who often have co-morbidities and run a higher r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
69
1
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 16 publications
0
69
1
11
Order By: Relevance
“…Thoracoscopic surgery is associated with a reduced incidence in the perioperative complications of lung cancer, and it is now feasible for very elderly people previously considered unsuitable for surgery due to the high risks involved to now be treated surgically. However, there are greater possibilities of prolonged postoperative hospital stays for elderly patients, together with increased intensive care unit (ICU) admission rates, and increased 30 day readmission rates and mortality following lung cancer surgery . Enhanced recovery after surgery (ERAS) is a multiprofessional, multidisciplinary and evidence‐based approach that aims to lessen surgical stress response, reduce complications, lower medical costs, and promote patient recovery through optimizing a series of perioperative management measures.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thoracoscopic surgery is associated with a reduced incidence in the perioperative complications of lung cancer, and it is now feasible for very elderly people previously considered unsuitable for surgery due to the high risks involved to now be treated surgically. However, there are greater possibilities of prolonged postoperative hospital stays for elderly patients, together with increased intensive care unit (ICU) admission rates, and increased 30 day readmission rates and mortality following lung cancer surgery . Enhanced recovery after surgery (ERAS) is a multiprofessional, multidisciplinary and evidence‐based approach that aims to lessen surgical stress response, reduce complications, lower medical costs, and promote patient recovery through optimizing a series of perioperative management measures.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced recovery after surgery (ERAS) is a multiprofessional, multidisciplinary and evidence‐based approach that aims to lessen surgical stress response, reduce complications, lower medical costs, and promote patient recovery through optimizing a series of perioperative management measures. Accumulating studies have shown that the elderly can benefit from the ERAS program . Geriatric patients with lung cancer often exhibit associated comorbidities than younger patients, thus necessitating more evaluation and care.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1995, Kehlet and colleagues reported that hospital stay was reduced to 2 days in a group of elderly high-risk patients undergoing laparoscopic colonic surgery by early aggressive perioperative care such as early oral nutrition and mobilisation 1 . ERAS for patients with colorectal surgery results in improved patient satisfaction, less variation in the patient care, reduced postoperative complication rates, earlier mobilisation and resumption of normal diet, shorter length of stay in hospital, reduced readmission rates, while ensuring patient safety and costeffectiveness [2][3][4] . ERAS has been used for many major operations across specialties including gastric/oesophageal, orthopaedics, urology, thoracic, etc.…”
Section: Introductionmentioning
confidence: 99%